Physiological, proteomic and metabolomic analysis provide insights into Ca2+ tolerance in Drynaria roosii leaves - Yilin Wu; Hongna Ma; Shanshan Ma; Weizhong Li; Longyan Tan (Plant Stress, 2023)
The specific mechanisms by which Ca2+ affects vegetative growth of plants in karst area are still unclear. The aim of the current experiment was to study the effects of excessive Ca2+ on physiological characteristics, proteins and metabolites of leaves of two-year old Drynaria roosii for 14 days and provide a theoretical reference for analyzing the mechanisms of the interaction between high concentration Ca2+ and vegetative growth of plants in karst area. We sought to investigate the effect of 0 mM Ca2+, 600 mM Ca2+, and 1200 mM Ca2+ on the properties of leaves of D. roosii. Physiological analysis reveals that excessive Ca2+ might inhibit the growth of D. roosii leaves by osmotic stress. Proteomics analysis suggests that differentially expressed proteins mainly involved in protein metabolism, amino acid metabolism, carbohydrate and energy metabolism, photosynthesis, antioxidant and defense. Metabolomics analysis indicates that differentially expressed metabolites mainly involved in amino acid metabolism, lignin biosynthesis, and flavonoid biosynthesis. These results give insights into the biological processes apparently involved in Ca2+ tolerance in this species.